HOW INSTAGRAM REELS SUPPORTS ENGLISH IDIOM LEARNING: AFFORDANCES AND CHALLENGES FROM EFL STUDENTS’ EXPERIENCES - Keisya Ersi Ivani; Nyimas Triyana Safitri; Hidayati (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
English Idioms as an Issue of EFL Teaching is a challenging one for EFL learners since most of idioms’ meaning is figurative and relative depending on its context. Following up on previous research which discusses Instagram Reels as the new way for English learners to acquire the vocabulary since it contains a very interesting short-form audio visual contents, this research explored how Instagram Reels facilitate EFL students’ English idiom learning process through exploring the affordances and challenges. This study was a qualitative case study which recruited five EFL learners in the second semester from Universitas Jambi who were selected using purposive sampling technique. The data collection instruments are semi-structured interviews which were analyzed using thematic analysis. The results demonstrate that there are six affordances of Instagram Reels on English idiom learning: repeated exposure to idiomatic expressions, multimodal support for interpreting figurative meanings, opportunities for autonomous learning, flexible access to learning, contextualized language input, and opportunities to use idioms in authentic communication. In addition to the affordances, the students also reported challenges: interpretation problem on the meaning, inadequate explanations from content creator, the rapidly vanished subtitle, and lack of feedback. Therefore, the results imply that Instagram Reels is a useful supplemental tool for EFL idiom learning; however teacher-based instructions are needed to enhance the understanding on difficult idioms.